2019
DOI: 10.1177/2042018819865828
|View full text |Cite
|
Sign up to set email alerts
|

Shared and unique risk factors for depression and diabetes mellitus in a longitudinal study, implications for prevention: an analysis of a longitudinal population sample aged ⩾45 years

Abstract: Objective: The objective of this study was to examine shared and unique risk factors for incident depression and diabetes mellitus in a national longitudinal population-based survey. Methods: Canadian National Population Health Survey (NPHS) longitudinal study was used. A subsample of the initial NPHS sample ( n = 4845), free of depression or diabetes mellitus at baseline was tracked over a 10-year period. Univariate and multivariate modified Poisson regression models were used to estimate the relative risk (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…The association of depression and DM worsens the general outcome related to DM, impairs adherence to medical treatment [ 12 ], decreases quality of life [ 13 ] and increases fatality [ 14 ]. There are many identified risk factors that increase the possibility of depressive symptoms emerging among patients with DM; these include age, gender, urban residence, glycaemic control, smoking, obesity and family history of depression [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association of depression and DM worsens the general outcome related to DM, impairs adherence to medical treatment [ 12 ], decreases quality of life [ 13 ] and increases fatality [ 14 ]. There are many identified risk factors that increase the possibility of depressive symptoms emerging among patients with DM; these include age, gender, urban residence, glycaemic control, smoking, obesity and family history of depression [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 Both conditions share relatively similar risk factors, including, age, obesity, reduced physical activity, diet, smoking, and alcohol. 3 4 T2DM is often considered an independent risk factor for the progression of colorectal cancer. 5 The risk of colon cancer increases by 40 to 60% in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies indicated a significant correlation between hypertension and depression in old adults in community-based studies 20 and indicated that a diastolic blood pressure difference of 5 mmHg significantly reduces the complications of death from diabetes and cerebral infarcts and the development of microvascular complications 21 . Physical inactivity, overweight/obesity, daily smoking, and hypertension have recently been demonstrated to be shared, and unique risk factors of DM and depressive disorders 22 . Diabetes and depression comorbidity significantly increase micro- and macrovascular complications 23 , 24 , elevated health care use 25 , and death rates 26 .…”
Section: Introductionmentioning
confidence: 99%